2020
DOI: 10.1101/2020.08.31.276733
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variation in the Gut Microbiota of Common Marmosets: Differences with Colony of Origin and Integration

Abstract: Characterization of the gut microbiome may aid understanding and management of natural and experimental disease states in research animals, thereby promoting reproducibility. In this study, the rectal bacterial communities of three separate common marmoset (Callithrix jacchus) breeding colonies were defined using 16S rRNA sequencing of rectal swab samples. Study animals originated from two German colonies and a United States colony (JHU). The two German cohorts, previously fed the same diet, were imported into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Using a small number of individuals, or animals from a single research colony or location is not sufficient, as demonstrated by the large effects of research facility in mice (95) and primates (96), and the large variation across studies in companion animals (97). Ideally, sampling of many individuals of diverse genetic backgrounds from multiple locations is suggested (89).…”
Section: Comparing To a "Normal" Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Using a small number of individuals, or animals from a single research colony or location is not sufficient, as demonstrated by the large effects of research facility in mice (95) and primates (96), and the large variation across studies in companion animals (97). Ideally, sampling of many individuals of diverse genetic backgrounds from multiple locations is suggested (89).…”
Section: Comparing To a "Normal" Microbiomementioning
confidence: 99%
“…Microbiome studies on other laboratory animals, including rodents and primates, suggests that results obtained from microbiome studies on colony animals might be difficult to replicate with animals from a different colony. Animals from different vendors or facilities, even if they are extremely similar genetically, have different microbiomes (95,96,147). The "vendor effect" can be larger than the effect of diet (95) and can impact multiple body systems (e.g., the immune system) (148,149).…”
Section: Colony Animals: Drawbacksmentioning
confidence: 99%
“…Studies revealed that the phyla Actinobacteria , Bacteroidetes , Firmicutes , Fusobacteria , and Proteobacteria are abundant in individuals without diseases [see 17 for a review], although high variability has been noted among facilities. The gut microbiome of primates is modulated by various factors, including diets [ 13 , 21 , 22 ], housing conditions [ 23 ], pairing [ 24 ], aging [ 15 ], and diseases [ 11 , 25 ]. Among them, diet is influential even for only a short period of time.…”
Section: Introductionmentioning
confidence: 99%